Liberalización, reestructuración productiva y competitividad en la industria peruana de los años 90 - Jiménez, Félix (1999)
This essay shows that the neoliberal adjustment program has reprimarized the Peruvian economy and has truncated the industrialization process. As a result of this adjustment, the manufacturing industry has lost its leadership and its international competitiveness, and the externa1 bottleneck has been exacerbated. The productive structure created by such policies has been unable to generate enough number of jobs, even when the economy was growing during 1993-1995 and 1997. Moreover, the new productive structure does not reflect either to be part of a restructuring process oriented to solve the old fundamental problems of the Peruvian  economy. With the reprimarization, the Peruvian economy comes into the XX1 century, with the same problems of the 5Os, but worsened by the negative effects of neoliberal policies on the manufacturing industry, on the leve1 of employment and income and, consequently, on the quality of life of a large number of people.